An unusual presentation of patent urachus: Report of a case - Ozel, SK; Kazez, A; Akpolat, N (Georg Thieme Verlag Kg, 2004)
Congenital umbilical disorders are frequently seen in the pediatric population and are mostly classified as retained umbilical cord structures or failure of umbilical ring closure. Vitelline duct anomalies, urachal anomalies and umbilical herniations comprise the main group of these congenital problems. Here we report a new presentation of vesicoumbilical patency in a 20-day-old male baby. A brief review of the literature concerning the classification of patent urachus to explain the possible mechanism of the anomaly is given.
Keywords: umbilicus; patent urachus; newborn